ANIMAL TURN AS A META-TURN? - MAMZER, HANNA (Society Register, 2019)
Human sciences as a reflection of social transformations fluctuate with dynamic changes of current cognitive paradigms. Following the textual and visual turn and the turn towards things (objects), there are intensified tendencies to think in terms of an “animal turn”, which becomes close not only to activists and pro-animal activists but also to scientifically engaged humanists. I believe, however, that the animal turn should be treated as a meta-turn: a process that requires a change in the relationship between the reflecting subject and the object of reflection, and not only as a specific kind of representation of the surrounding world. In the proposed text, I attempt to analyze the causes of the turn towards animals. I also address the theme of cognitive resistance in view of the recognition of animal studies as a fully-fledged theoretical and research area of contemporary humanities.